Real World Outcomes of Ipilimumab and Nivolumab in Patients with Metastatic Melanoma - Asher, Nethanel (Cancers (Basel), 2020)
Background: Immunotherapy has drastically changed the outlook for melanoma patients over the past decade. Specifically, the dual blockade of immune checkpoints using ipilimumab and nivolumab has shown unprecedented response rates and survival outcomes. This immense achievement, though, is at the cost of toxicity, with 60% of the patients experiencing high-grade adverse events (AEs). Our study aims to report the efficacy and toxicity outcomes of an out-of-trial, real-life population. Methods: Data on metastatic melanoma patients treated with ipilimumab and nivolumab were retrieved from our melanoma database—a single-center prospectively updated, medical-records based oncologic registry. Data included demographics, clinical and pathological information, as well as tumor responses and survival. Associations between patient or treatment characteristics and outcomes were also evaluated. Results: We identified 172 metastatic melanoma patients, of whom 64% were treatment-naïve. The median follow-up was 12 months. The response rates for treatment-naïve and previously-treated patients were 61% and 25%, respectively; median progression-free survival (PFS) were 12.2 and 2.6 months, and median overall survival (OS) were not-reached (NR) and 6.1 months, respectively. The estimated three-year OS for treatment-naïve patients was 58% (95% CI 42–65). At data cutoff, 22% were still on-treatment. Grade 3–4 adverse events (AEs) were reported in 60% of the patients, almost all of whom were exposed to steroid treatments (59%); AEs were fatal in 4 patients, and led to permanent treatment discontinuation in 31%. Factors significantly associated with outcome were cutaneous histology, low lactate dehydrogenase (LDH), low number of metastatic sites, performance status, first line of treatment and number of combinations administered during the induction phase. Conclusions: Despite the profoundly different baseline patient characteristics, the combination of ipilimumab and nivolumab is as effective in the real-world population as it was in clinical trials, including long-term outcomes. In addition to confirming the significance of baseline prognostic factors, our study reveals that the number of combinations effectively administered may also be correlated with good outcome.